The small RNA repertoire of Dictyostelium discoideum and its regulation by components of the RNAi pathway - Hinas, Andrea (Oxford University Press, 2007)
Small RNAs play crucial roles in regulation of gene expression in many eukaryotes. Here, we report the cloning and characterization of 18–26 nt RNAs in the social amoeba Dictyostelium discoideum. This survey uncovered developmentally regulated microRNA candidates whose biogenesis, at least in one case, is dependent on a Dicer homolog, DrnB. Furthermore, we identified a large number of 21 nt RNAs originating from the DIRS-1 retrotransposon, clusters of which have been suggested to constitute centromeres. Small RNAs from another retrotransposon, Skipper, were significantly up-regulated in strains depleted of the second Dicer-like protein, DrnA, and a putative RNA-dependent RNA polymerase, RrpC. In contrast, the expression of DIRS-1 small RNAs was not altered in any of the analyzed strains. This suggests the presence of multiple RNAi pathways in D. discoideum. In addition, we isolated several small RNAs with antisense complementarity to mRNAs. Three of these mRNAs are developmentally regulated. Interestingly, all three corresponding genes express longer antisense RNAs from which the small RNAs may originate. In at least one case, the longer antisense RNA is complementary to the spliced but not the unspliced pre-mRNA, indicating synthesis by an RNA-dependent RNA polymerase.